(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2017)
Many years have passed since the rise and consolidation of third generation therapies as part of cognitivebehavioral therapies. The application of those involve the development of specific therapeutic skills that differ partially from those used in other models, one of them is the daily and constant exercise to become a mindful therapist. Being a mindful therapist requires openness to oriental philosophies and enhancing contemplative experiences in everyday life. The Latin American context presents particularities that limit the adequate execution of third generation therapies. Among the therapist’s difficulties are the insuficiente specialized education, the overestimation of the first and second-generation models, ignorance and apathy towards the effort to be a mindful therapist, the scarce knowledge and underestimation of the oriental philosophies that sustain mindfulness, and the economic deficiencies and lack of opportunities for many therapists committed to their education. Regarding the limitations of the context are the predominant religiosity with locus of external control, the mistrust of psychological interventions based on meditation, and the inaccessibility to the popular sectors of the population.